Improving year-round protection against influenza infection in the tropics - Young, Barnaby (Nanyang Technological University, 2022)
Influenza is a common infection in the tropics and a major cause of morbidity and mortality, with a burden of disease which is comparable to temperate climates. Vaccination is the main pharmacological method available to reduce transmission and prevent infection, but evidence that vaccine induced protection with the standard dose inactivated influenza vaccine lasts year-round is lacking. This thesis presents a review of influenza epidemiology in Asia and the association between the pattern of seasonality and latitude and climate; a systematic review and meta-analysis of test-negative design (TND) case-control studies in order to generate summary estimates of changes in vaccine effectiveness with time since vaccination; results of a cohort study that investigates whether there is evidence for waning vaccine protection against severe influenza in Singapore; an observer-blind randomised clinical trial of annual versus biannual influenza vaccination in older adults, and further analysis of predictors of waning antibody titres post-vaccination.